Problematyka kontraktów długoterminowych w procesie nauczania rachunkowości - Kasperowicz, Anna (Position and Role of the Long-Term Contracts in Process of Teaching Accountancy, 2005)
The main target of implementing long-term contracts as a separate item is complex presentation of problems of finance accounting, tax accountancy, reporting accountancy and management accountancy as well, with close connection with the specificity of services realized through a few accountancy periods. Pricing of long-term contracts is not only a problem of big companies with very well developed big accountant departments. Much more often problems of pricing appear in small companies, in which this pricing has very big influence on financial picture of those companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 72-75